Characterization of carboxylic acid reductase from Mycobacterium phlei immobilized onto Seplite LX120 - Basri, Rose Syuhada; Raja Abd. Rahman, Raja Noor Zaliha; Ahmad Kamarudin, Nor Hafizah; Latip, Wahhida; Mohamad Ali, Mohd Shukuri (MDPI, 2022)
A multi-domain oxidoreductase, carboxylic acid reductase (CAR), can catalyze the one-step reduction of carboxylic acid to aldehyde. This study aimed to immobilize bacterial CAR from a moderate thermophile Mycobacterium phlei (MpCAR). It was the first work reported on immobilizing bacterial CAR onto a polymeric support, Seplite LX120, via simple adsorption. Immobilization time and protein load were optimized for MpCAR immobilization. The immobilized MpCAR showed optimal activity at 60 °C and pH 9. It was stable over a wide range of temperatures (10 to 100 °C) and pHs (4–11), retaining more than 50% of its activity. The immobilized MpCAR also showed stability in polar solvents. The adsorption of MpCAR onto the support was confirmed by Scanning Electron Microscopy (SEM), Fourier-Transform Infrared (FTIR) spectroscopy, and Brunauer–Emmett–Teller (BET) analysis. The immobilized MpCAR could be stored for up to 6 weeks at 4 °C and 3 weeks at 25 °C. Immobilized MpCAR showed great operational stability, as 59.68% of its activity was preserved after 10 assay cycles. The immobilized MpCAR could also convert approximately 2.6 mM of benzoic acid to benzaldehyde at 60 °C. The successfully immobilized MpCAR on Seplite LX120 exhibited improved properties that benefit green industrial processes.